Serodiversity of opsonic antibodies against Enterococcus faecalis--glycans of the cell wall revisited. - Christian Theilacker (Public Library of Science (PLoS), 2011)
In a typing system based on opsonic antibodies against carbohydrate antigens of the cell envelope, 60% of Enterococcus faecalis strains can be assigned to one of four serotypes (CPS-A to CPS-D). The structural basis for enterococcal serotypes, however, is still incompletely understood. Here we demonstrate that antibodies raised against lipoteichoic acid (LTA) from a CPS-A strain are opsonic to both CPS-A and CPS-B strains. LTA-specific antibodies also bind to LTA of CPS-C and CPS-D strains, but fail to opsonize them. From CPS-C and CPS-D strains resistant to opsonization by anti-LTA, we purified a novel diheteroglycan with a repeating unit of →6)-β-Galf-(1→3)- β-D-Glcp-(1→ with O-acetylation in position 5 and lactic acid substitution at position 3 of the Galf residue. The purified diheteroglycan, but not LTA absorbed opsonic antibodies from whole cell antiserum against E. faecalis type 2 (a CPS-C strain) and type 5 (CPS-D). Rabbit antiserum raised against purified diheteroglycan opsonized CPS-C and CPS-D strains and passive protection with diheteroglycan-specific antiserum reduced bacterial counts by 1.4-3.4 logs in mice infected with E. faecalis strains of the CPS-C and CPS-D serotype. Diheteroglycan-specific opsonic antibodies were absorbed by whole bacterial cells of E. faecalis FA2-2 (CPS-C) but not by its isogenic acapsular cpsI-mutant and on native PAGE purified diheteroglycan co-migrated with the gene product of the cps-locus, suggesting that it is synthesized by this locus. In summary, two polysaccharide antigens, LTA and a novel diheteroglycan, are targets of opsonic antibodies against typeable E. faecalis strains. These cell-wall associated polymers are promising candidates for active and passive vaccination and add to our armamentarium to fight this important nosocomial pathogen.